The effects of enforced reflection in three simple experiments - Björn Frank (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
Rubinstein (2007) has recently found that the frequency of (types of) decisions made in Internet experiments are related to the time taken for these decisions. Other authors have investigated this relationship by exerting some time pressure. In this paper, I report on an attempt to do the opposite, i.e., to enforce a longer reflection time. To ensure that subjects do not just wait but actually think for five minutes, they had to perform a five minutes focused free writing task. Free writing is a standard method adopted from creative writing courses; subjects are asked to write up everything that currently runs through their minds, without pausing. Enforced reflection significantly decreases the number chosen in beauty contest experiments, thus increasing the winning probability, and it increases the amount given in the solidarity game. For women, this increase is economically and statistically significant. The average amount offered in the ultimatum game is not higher for those who had performed the free writing task. However, after free writing, the share of 50:50 offers is significantly higher, which is in conflict with Rubinstein's conjecture that 50:50 offers take less time because they are instinctive (as opposed to cognitive).
Keywords: C90; D03; 330; free writing; decision time; beauty contest; solidarity game; ultimatum game; Entscheidung; Zeit; Verhaltensökonomik; Ultimatumspiel; Test